الكفاءة في الزواج : على ضوء منظور الشريعة الإسلامية و تطبيقها في المجتمع ا الإسلامي في إندونيسيا - Irham Dongoran; Heri Firmansyah (Sufiya Research Institute, 2023)
This research tries to find out how the concept of kafaah in Islam and its application in marriages in Indonesian Muslim society. In this study, the area used as the research sample was Barus District, Central Tapanuli Regency, North Sumatra. The sample used in this study were 3 people or three couples who had their own problems when they were going to get married because of rejection from the families of the bride and groom. In this study, it was found that the problem of kafaah was not caused by religion, but was caused by work and ethnicity. In fact, according to madhhab scholars, kafaah in Islam which is very important is a matter of religion.